The effect of unemployment and economic growth on poverty in West Sumatra Province - Hendri Andika Saputra; Dastanta Irvan Ginting; Sukardi Sukardi; Ahmad Albar Tanjung (International Journal of Applied Finance and Business Studies, 2023)
Poverty is a global issue faced by countries worldwide, defined as the inability to attain minimum living standards. This research aims to explore the impact of unemployment and economic growth on poverty in the province of West Sumatra. The study employs the Error Correction Model (ECM) approach. The analysis reveals that the unemployment variable has a positive and significant influence on the unemployment rate in both the short and long term. Additionally, the economic growth variable has a positive and significant impact on poverty in the long term. These findings shed light on the intricate dynamics between unemployment, economic growth, and poverty in West Sumatra, providing valuable insights for policymakers striving to develop effective and sustainable strategies to address poverty in the region.